Outcome of traumatic brain injury and its associated factors among pediatrics patients treated in Amhara national regional state comprehensive specialized hospitals, Ethiopia 2022. - Getabalew, Aytenew; Mekonnen, Kennean; Liyew, Bikis; Alemayehu, Abebaw; Melesegn, Belete (Journal of Spine and Neuroscience, 2023)
Background Traumatic brain injury in pediatrics is one of the commonest causes of morbidity, disability and mortality worldwide. In low- and middle-income countries Study showed that death of pediatrics from traumatic brain injury was 7.3%. However, there is limited data towards the outcome of traumatic brain injury and its associated factors in Ethiopia. Objective To assess the outcome of traumatic brain injury and associated factors among pediatrics patients in Amhara National Regional State Comprehensive Specialized Hospitals, Ethiopia. Methods An institution based retrospective cross-sectional study was conducted among 423 pediatrics patients from January 1, 2019 to December 30, 2021, and data extraction period was from May 16 to June15, 2022. Systematic random sampling technique was employed to select the study participants. Data were collected from patient charts and registry books by using a data extraction tool. Data were entered into the Epi-info version 7 and analysis was done by SPSS Version 25. Both Bi-variable and multi-variable analyses were employed to identify factors associated with outcome of traumatic brain injury. Result From 423 sampled study participant charts 404 of them had complete information with response rate of 95.5% and included in the final analysis. The overall unfavorable outcome of traumatic brain injury at discharge was found that 12.13% (95% CI: 9.1% - 15.7 %). Sever traumatic brain injury (AOR: 5.11(CI :1.8-14.48), moderate traumatic brain injury (AOR:2.44(CI:1.07-5.58), Hyperglycemia (AOR: 3.01 (CI:1.1-8.04), sign of increased intracranial pressure (AOR:7.4(CI:3.5-15.26), and medical comorbidity (AOR: 2.65(CI:1.19-5.91) were predicted of unfavorable outcome of traumatic brain injury pediatrics patient. Conclusion and recommendations twelve present of traumatic brain injury results unfavorable outcome. Sever and moderate form of traumatic brain injury, hyperglycemia, signs of increased intracranial pressure, and medical comorbidity were factors associated with unfavorable outcome of traumatic brain injury in children. Therefore, it is preferable to improve accesses to acute and post-acute care services to lower the unfavorable outcome of traumatic brain injury in children.
Keywords: Traumatic Brain Injury; Pediatrics; Associated Factors; Amhara Regional State